2020
DOI: 10.1177/1357633x20914445
|View full text |Cite
|
Sign up to set email alerts
|

Video-interpreting for cognitive assessments: An intervention study and micro-costing analysis

Abstract: Introduction Evidence in the literature demonstrates the reliability of cognitive screening assessments using video technology in English-speaking older populations. However, this has not been tested in older culturally and linguistically diverse (CALD) populations who require an interpreter, and what the associated costs would be. The aim was to determine if the Rowland Universal Dementia Assessment Scale (RUDAS) and the Geriatric Depression Scale (GDS) could be reliably administered over video-interpreting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
(33 reference statements)
0
14
0
1
Order By: Relevance
“…Furthermore, Wadsworth and colleagues [ 12 ] demonstrated that commonly used cognitive tests, when performed through telemedicine, could distinguish between patients with and without dementia. Hwang K et al [ 13 ] demonstrated that the virtual interpretation of tests score is also cheaper than the face-to-face one. It is mainly observed in their preliminary cost analysis, a saving of approximately 250,000 Australian Dollars per year (when considering a medium spare of seven dollars per session).…”
Section: Telemonitoring In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Furthermore, Wadsworth and colleagues [ 12 ] demonstrated that commonly used cognitive tests, when performed through telemedicine, could distinguish between patients with and without dementia. Hwang K et al [ 13 ] demonstrated that the virtual interpretation of tests score is also cheaper than the face-to-face one. It is mainly observed in their preliminary cost analysis, a saving of approximately 250,000 Australian Dollars per year (when considering a medium spare of seven dollars per session).…”
Section: Telemonitoring In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Therefore, since care should be provided to confined patients in rural areas of Chile, where access to medical care is limited 60 , our working group designed a strategy for TNP assessment. First, to use cognitive tests that could be used through virtual platforms and that the cognitive tests available for use using video technologies were fast, efficient, and reliable 12 , they should be adapted and implemented in culturally diverse populations, with low educational levels or illiterate 61 . In this order of ideas, the PT would meet the conditions to be administered to detect CD and dementia in elderly people with a low educational level or illiterate through TNP.…”
Section: Dement Neuropsycholmentioning
confidence: 99%
“…For example, Havelka [14] reported that in Austria interpreters for VMI service were required to be available within 120 seconds. Besides, the time it took users to schedule interpreting service (i.e., the period after one sends out a service request and before one successfully books the service) seemed to be shorter in VMI than on-site, since in VMI one did not have to waste time for rescheduling when no on-site interpreter was available in the initial desired time and/or place [15].…”
Section: Review Of Research Designs and Research Findingsmentioning
confidence: 99%
“…Another important topic of VMI research is financial cost of VMI and extra financial benefits that interpreters and/or users of interpreting service can obtain by using VMI instead of on-site or telephone interpreting, on which the relevant findings so far were comparatively consistent. According to the reviewed articles (e.g., [11,15]), VMI reduced overall financial cost for organizations (e.g., hospitals, police stations) that had a constant need of interpreting service and usually required the service to be available on short notice, although the capital cost for VMI devices could be expensive; to interpreters, as VMI saved travel distance and travel time, this interpreting mode could help them not only save the financial cost for travelling, but also better meet the high demand in interpreting work and thus get more financial benefits; to individuals who needed interpreting service (e.g., a patient who was a sign language user and had to communicate with a healthcare provider who did not know the sign language), VMI was less expensive than on-site interpreting. Even in some cases where VMI was more expensive than telephone interpreting, patients were still more willing to use VMI since it provided more visual information than telephone interpreting, which is important in communication.…”
Section: Review Of Research Designs and Research Findingsmentioning
confidence: 99%